CREATION OF INNOVATIVE APPROACH FOR STUDY OF THE NATIONAL FISCAL SPACE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The choice and topicality of the theme is substantiated by the fact that a sustainable development of a country is affected by the policy implemented by the government. One of its main parts is the fiscal or budget policy which means the formation of the necessary funds of the revenues and expenditures to ensure the functioning of the government. Accordingly, the concept of fiscal space has been activated which is closely connected with the implementation of the instruments of fiscal policy (taxes, government expenditures, government debt). The aim of the research is to create an innovative approach to the investigation of the creation of the state fiscal space applying the simulation method in the environment of Matlab/Simulink in order to forecast the influence of the corporate income tax on the state economic and financial indicators taking into account the changes of the corporate income tax offered by the government and the Bank of Latvia. Methodology of the research implies the following activities: the identification of the concept of fiscal space and its application in the context of the influence on economy; the creation of the assessment methodology of the components of fiscal space using technological tools (data modelling in Matlab / Simulink environment).